The prophets : introducing Israel's prophetic writings - Cook, Stephen L., 1962-; Strong, John T.; Tuell, Steven Shawn (Fortress Press, 2022)
The prophets remain figures of enduring interest and importance in contemporary Judaism, Christianity, and even secular society. The Prophets introduces students to the rise of prophecy in ancient Israel, possible ancient Near Eastern parallels, the messages of individual prophets, and the significance of the compositional and editorial history of the prophetic writings. The book guides students into leading questions and issues in contemporary scholarship, and surveys different contemporary approaches to the messages of the prophets. Part 1 introduces the prophets and prophecy in context. The rise of prophecy, the role of the prophet, key themes, and the fate of prophecy are explored. Part 2 profiles Israel's prophets during the eighth century, the exile, and the postexilic period. This section will also look at each book of the prophets and how the prophetic writings fit within the complete Hebrew Bible and the Old Testament. These chapters also provide insights into interpreting the prophetic writings today, including Jewish and Christian interpretations, prophecy and prediction, and the secular legacy of Israelite prophecy. This textbook includes numerous images, charts, and maps to enhance the experience of the students.
Part I. Approaching ancient Israel's prophets. Introduction to the prophetic writings -- The historical setting of the Israelite prophets -- Part II. The prophetic literature. Isaiah -- Jeremiah -- Ezekiel -- Hosea -- Joel -- Amos -- Obadiah -- Jonah -- Micah -- Nahum -- Habakkuk -- Zephaniah -- Haggai -- Zechariah -- Malachi -- Daniel.
Includes bibliographical references and index.
Keywords: Bible. -- Introductions; Bible; Prophecy -- Biblical teaching; Prophétie.; Prophecy; Prophecies